ENHANCING EMPLOYEE PERFORMANCE THROUGH ENGAGEMENT AND COMMITMENT: THE MEDIATING ROLE OF WORK MOTIVATION - Rosidi, Imron; Enawar, Enawar; Uttami, Mega; Nasution, Donni Alnis (Dynamic Management Journal, 2025)
This study examines the influence of employee engagement and organizational commitment on employee performance at PT. Tatimel Maitoya, a company operating in a competitive industrial environment where human capital efficiency is critical. The research aims to understand how psychological and attitudinal factors drive workforce productivity in a manufacturing setting. Using a quantitative approach with a saturated sample of 75 employees, data were collected through structured questionnaires and analyzed using multiple linear regression with SPSS. Results indicate that both employee engagement and organizational commitment have a significant positive impact on employee performance, individually and collectively, with a high explanatory power. The study contributes to organizational behavior literature by confirming the relevance of engagement and commitment in an Indonesian corporate context. Its novelty lies in focusing on a less-explored firm in the regional manufacturing sector, offering practical insights for HR strategies aimed at enhancing performance through non-financial motivators.